2012
DOI: 10.1186/1471-2458-12-989
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of dental caries predictors in 6-year-old school children - results from 5-year retrospective cohort study

Abstract: BackgroundThis was a retrospective cohort study undertaken to assess the rate and pattern of dental caries development in 6-year-old school children followed-up for a period of 5 years, and to identify baseline risk factors that were associated with 5 years caries experience in Malaysian children.MethodsThis 5-years retrospective cohort study comprised primary school children initially aged 6 years in 2004. Caries experience of each child was recorded annually using World Health Organization criteria. The rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
1
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 13 publications
1
30
1
6
Order By: Relevance
“…Epidemiological studies indicate that prevalence of ECC is quite high in pre-school (2-5 years) children and this tended to increase with age [4,8,9]. Prevalences of ECC were found to be 27-44 % in India, 32-36 % in Brazil, 40 % in Malaysia and 48-94 % in Mexico [2,[10][11][12][13][14][15]. In Turkey, the prevalences were reported to be between 17.3-69.8 % [3,4,16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies indicate that prevalence of ECC is quite high in pre-school (2-5 years) children and this tended to increase with age [4,8,9]. Prevalences of ECC were found to be 27-44 % in India, 32-36 % in Brazil, 40 % in Malaysia and 48-94 % in Mexico [2,[10][11][12][13][14][15]. In Turkey, the prevalences were reported to be between 17.3-69.8 % [3,4,16,17].…”
Section: Discussionmentioning
confidence: 99%
“…In broader scenarios, clustering can be seen in any setting, for example, in social settings (e.g., individuals → families → neighborhoods) or in geographical settings (e.g., wards → cities → counties → countries). In addition, in longitudinal studies or clinical trials, clustering appears due to aggregates of individuals or repeated measurement of the same subject (Masood, Yusof, et al 2012a, 2012bFleming et al 2013). However, in dental research, a special type of natural clustering is encountered, where surfaces are clustered within teeth and teeth clustered within individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, in most industrialized countries the prevalence of dental caries has varied [Petersen, 2003;Marthaler, 2004]. Studies on the etiology of dental caries have shown that small population groups maintain a high prevalence of this disease [Ueda et al, 2004;Masood et al, 2012], and others reported that the disparity of disease may be related to a more intense exposure to risk factors (gender, educational level of mothers, SES, oral hygiene habits, fluoride history, dental fluorosis, access to oral health services, sugar consumption, diet habits, area of residence) and to social deprivation [Patrick et al, 2006;Sabbah et al, 2009].…”
mentioning
confidence: 99%